2020
DOI: 10.3390/d12090358
|View full text |Cite
|
Sign up to set email alerts
|

A Hot Spot of Olive Biodiversity in the Tunisian Oasis of Degache

Abstract: Tunisia is one of the world’s largest producers of olive oil, and it preserves pools of olive genetic diversity that are still unexplored. A recent prospection and collection program of the National Gene Bank of Tunisia (NGBT) focused on the vast oasis of Degache, in the south west part of Tunisia, where 47 samples were collected and genetically characterized through simple sequence repeat (SSR) markers. Identification and authentication of genotypes were obtained through comparison with reference cultivars be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…On the contrary, focusing on the characterization of South East Tunisian germplasm, Ben Mohamed et al [ 76 ], and Ben Ayed et al [ 77 ] highlighted a lack of correlation between genetic and geographical origin of olive cultivars in Tunisia. Other authors [ 78 ] have shown the clustering of cultivars from the same or a nearby region, suggesting a common genetic base of these cultivars. This is in agreement with the hypothesis of autochthonous origin of most of the olive cultivars as well as their limited diffusion from their centers of origin [ 79 ].…”
Section: Olive Genetic Resources Characterization and Study Of Genmentioning
confidence: 86%
See 1 more Smart Citation
“…On the contrary, focusing on the characterization of South East Tunisian germplasm, Ben Mohamed et al [ 76 ], and Ben Ayed et al [ 77 ] highlighted a lack of correlation between genetic and geographical origin of olive cultivars in Tunisia. Other authors [ 78 ] have shown the clustering of cultivars from the same or a nearby region, suggesting a common genetic base of these cultivars. This is in agreement with the hypothesis of autochthonous origin of most of the olive cultivars as well as their limited diffusion from their centers of origin [ 79 ].…”
Section: Olive Genetic Resources Characterization and Study Of Genmentioning
confidence: 86%
“…The research pointed out, in this unknown germplasm, gene pools not present in commercial (Nurseries) varieties, underlining the need to broaden the genetic base of the commercialized germplasm to avoid genetic erosion of this olive patrimony. In addition, Saddoud Debbabi et al [ 78 ] the genetic diversity of the olive germplasm of the oasis of Degache, in the south west part of Tunisia, characterized by arid climate and low pluviometry (<100 mm/year), showing the presence of olive genotypes largely diverse from the reference germplasm, including the traditional cultivar of Chetoui and Chemlali, but also from other modern varieties [ 78 ]. The population structure analysis identified two gene pools more represented in germplasm from southern Tunisia, where environmental conditions at critical plant development phases, are harsher.…”
Section: Olive Genetic Resources Characterization and Study Of Genmentioning
confidence: 99%
“…In the last decades, the growing need to preserve the existing germplasm from genetic erosion resulted in the building of the large world germplasm collections, such as the World Olive Germplasm Banks (WOGB) at IFAPA (Cordoba, Spain) and Marrakech (Morocco), besides many small collections created in Europe [54,[107][108][109], Northern America [110,111], Southern America [112], Australia [113], Northern Africa [114][115][116][117], the Middle East [118,119], the Balkan area [24,120,121], Iberia [122,123]. SSRs have been the marker of choice for genotyping these genetic resources.…”
Section: Ssr Markermentioning
confidence: 99%
“…From all the studies about oleaster carried out so far, some key concepts have emerged and they are summarized in Table 2. The evaluation and characterization of local wild germplasm populations performed in these studies pointed out the great importance and relevance of these collections, as they represent a great source of genetic variability [14,47,74].…”
Section: Genetic Diversity Assessmentmentioning
confidence: 99%